A soft breaststroke-inspired swimming robot actuated by dielectric elastomers. (14th March 2019) - Wang, Shu; Huang, Bo; McCoul, David; Li, Mingyu; Mu, Lili; Zhao, Jianwen
Abstract: This article presents the design, fabrication, and performance of a swimming robot actuated by dielectric elastomer actuators (DEAs). The robot is inspirited by the breaststroke swimming maneuver and consists of two DEAs to mimic two swimming legs. A special structure was explored to mimic the foot, and the structure could adjust its deformation intelligently during the biomimetic breaststroke; as a result it is referred to as a self-adaptive foot in this paper. The robot has a simple and compact structure, weighing only 14.3 g and having overall dimensions of 100 mm × 123 mm × 66 mm (length × width × height). When a voltage is applied to the legs, the two legs gradually and rapidly form a semi-enclosed space the can effectively increase the forward propulsion. The self-adaptive feet can change their water-facing area based on the direction of the water pressure. When powered off, the self-adaptive feet produce almost no backward force, and can even produce a slight forward propulsion force. In order to verify swimming performance, a robot with self-adaptive feet was fabricated and compared to another robot without self-adaptive feet. The results showed that the swimming speed of the robot with self-adaptive feet was 3.15 times faster than the robot without self-adaptive feet at 2 Hz. The maximum swimming speed of the robot with self-adaptive feet was 0.77 body lengths per second at a driving frequency 1.5 Hz and the amplitude of the square waveform voltage at 4.8 kV. In addition, the swimming robot can realize agile turning motions when applying the voltage to only one of the legs. The minimum turning radius was about 70 mm.